TEACHER PERCEPTION RELATED TO WASAKA CHARACTER IMPLEMENTATION - Muhsinah Annisa; Fadhlan Muchlas Abrori; Prasetio, Teguh; Asrani; Herti Prastitasari; Jannah, Fathul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Teachers' perceptions of the character of Waja Sampai Kaputing (Wasaka) are intentionally or unintentionally influenced by character education. It consists of behaviourism, cognitivism, constructivism, habituation, and reward and punishment. This study aims to identify teachers' perceptions regarding implementing the Wasaka character. This research was an exploratory study using two quantitative and qualitative approaches. The results of this study indicated that the tendency of schools and teachers' experience leads more to learning activities that refer to the cognitive-constructivist learning model and habituation. It is closely related to the teachers' perception, where they used these two models more in the classroom. The teacher also believed that this model is in line with the character of Wasaka, which leads to assimilation and repetition of experiences, such as persevering, working hard, and others. This research is an early initiation with many limitations. In the future, it is hoped that further research with the expansion of data collection methods or additional participants can enrich this research data to make it more representative.